Identification of novel Jingmen tick virus from parasitic ticks fed on a giant panda and goats in Sichuan Province, southwestern China - Huang, Lin; Liu, Shunshuai; Chen, Lu; Wang, Fei; Ye, Ping; Xia, Luoyuan; Jiang, Baogui; Tang, Hao; Zhang, Qingyu; Ruan, Xiangdong; Chen, Weijun; Jiang, Jiafu (Frontiers in Microbiology, 2023)
Introduction Tick-borne viruses (TBVs) pose a significant risk to the health of humans and other vertebrates. A class of multisegmented flavi-like viruses, Jingmen tick virus (JMTV) was first discovered in Rhipicephalus microplus ticks collected from Jingmen of Hubei Province, China in 2010. JMTV has been confirmed to have a relatively wide distribution in vectors and hosts and is associated with human diseases. Methods Parasitic and host-seeking ticks were collected in Wolong Nature Reserve, Sichuan Province. Total RNA was extracted and then enriched the viral RNA. The DNA library was constructed and then were sequenced with MGI High-throughput Sequencing Set (PE150). After the adaptor sequences,low-quality bases and host genome were removed, resulting reads classified as a virus were subsequently de novo assembled into contigs, which were then compared to the NT database. Those annotated under the kingdom virus were initially identified as potential virus-associated sequences. Phylogenetic and Reassortment analysis of sequences were performed using MEGA and SimPlot software, respectively. Results and discussion Two host-seeking ticks and 17 ticks that fed on giant pandas and goats were collected. Through high-throughput sequencing, whole virus genomes were attained from four tick samples (PC-13, PC-16, PC-18, and PC-19) that shared 88.7–96.3% similarity with known JMTV. Phylogenetic tree showed that it was a novel JMTV-like virus, referred to as Sichuan tick virus, which also had the signals of reassortment with other JMTV strains, suggesting a cross-species transmission and co-infection of segmented flavi-like viruses among multiple tick hosts. Conclusion We discovered and confirmed one new Jingmen tick virus, Sichuan tick virus. Further investigation is required to determine the pathogenicity of Sichuan tick virus to humans and animals, as well as its epidemiological characteristics in nature.